## Differential Equation: $(1-xy)^{-2} dx + \left[ y^2 + x^2 (1-xy)^{-2} \right] dy = 0$

Hello, can anyone solve this equation?

I can't figure it out,

$(1-xy)^{-2} dx + \left[ y^2 + x^2 (1-xy)^{-2} \right] dy = 0$

Thanks.

Hello, can anyone solve this equation?

I can't figure it out,

$(1-xy)^{-2} dx + \left[ y^2 + x^2 (1-xy)^{-2} \right] dy = 0$

Thanks.

(x²+4) y' + 3 xy = x

- Read more about DE: $(x²+4) y' + 3 xy = x$
- Log in or register to post comments

(y^4 - 2xy) dx + 3 x^2 dy= 0

- Read more about bernoulli: $(y^4 - 2xy) dx + 3 x^2 dy= 0$
- 2 comments
- Log in or register to post comments

Please help me solve this Differential Equation

2ydx+x(x^{2}lny -1)dy=0

Please help me to solve this differential equation

ye^{xy}dx+xe^{xy}dy=0

xdx + sin^2 ( y/x ) [ ydx - xdy ] = 0

The given two-parameter family is a solution of the indicated differential equation on the

interval (−∞,∞). Determine whether a member of the family can be found that satisfies the

initial conditions.

y = c1e^x cos x + c2e^x sin x; y" − 2y' + 2y = 0,

i. y(0) = 1, y'(π) = 0

ii. y(0) = 1, y(π) = −1